The potential use of genomic methods in bottom trawl surveys to improve stock assessments in Europe - Rodríguez-Mendoza, Rebeca; Saborido-Rey, Fran (Frontiers in Marine Science, 2023)
In Europe, research surveys carried out by state governments provide the great majority of fishery-independent data. Member States (MS) in the European Union (EU) regularly conduct research surveys to provide the necessary data to assess the status of exploited fish stocks and to monitor the general condition of the marine ecosystem. In the surveys, samplings are carried out throughout the distribution range of the targeted fish species using standardized gears (e.g., trawls and seines) and other methods (e.g., hydroacoustics and underwater cameras). In the context of fish stock assessment, survey data are important because they provide indices that help tuning the stock assessment models (e.g., the index of fish abundance) and key information about the size and age distributions of the stock, the size-age relationships, the proportion of fish mature at each age, and information on reproductive performance of the stocks. However, research surveys have a number of shortcomings that include, for example, a high economic cost coupled with complex logistics and a long time required for processing the collected data. In addition, some of the parameters that are needed in stock assessment cannot be estimated from survey data for certain commercially important species. For instance, age is usually determined using hard structures (such as otoliths) in fish target species. However, for European hake, age cannot be determined accurately because there are many difficulties in interpreting the ring patterns of the otoliths. This highlights the need to look for alternative methodologies such as genomics, that have the potential of improving the data obtained from research surveys and hence, improve fish stock assessments. Considering this, we carried out a review of the bottom trawl research surveys in the EU with the purpose of: 1) identifying the current approaches for monitoring fishery resources and the ecosystem and 2) determining how genomic techniques can be used to improve survey data, taking into account the needs of current and future stock assessment in Europe.